Aqueous ozone: Chemistry, physiochemical properties, microbial inactivation, factors influencing antimicrobial effectiveness, and application in food. Issue 2 (24th January 2022) - Premjit, Yashaswini; Sruthi, N. U.; Pandiselvam, R.; Kothakota, Anjineyulu
Abstract: The need for sustainable food production and the demand for fresh and minimally processed foods have prompted remarkable research in novel food processing technologies that ensure safe and shelf‐stable food for a large population. Long‐established techniques such as heating, drying, and freezing have been associated with nutrient loss and high energy consumption. This trend has drawn attention to the practice of employing ozone in several food applications owing to its significant disinfectant and antimicrobial efficiency. The aqueous form of ozone has been found to show greater efficacy than its gaseous form, with faster decomposition rates leaving no harmful residues. The current study presents an overview of the latest scientific literature on the properties, chemistry, and generation of aqueous ozone, emphasizing the factors affecting process efficiency. The review scrupulously focuses on food decontamination, starch modification, pesticide degradation, and seed germination effects of aqueous ozone, highlighting the optimum processing parameters and salient findings of some major studies. A brief insight into the limitations and future trends has also been presented. Aqueous ozone has been acclaimed to have the potential to cause significant changes in the food matrix that could result in constructive modifications with outcomes entirely dependent on the processing conditions. Indirect and direct reactions involving hydroxyl radical and molecular oxygen atoms, respectively, form the basis of the ozone reaction in aqueous media, providing a distinctive kind of advanced oxidation process that offers certain crucial benefits. With a shorter half‐life in water as compared to air, the rapid decomposition of aqueous ozone to oxygen, leaving no harmful residues, adds to its advantages.